Validated HPLC Method for Simultaneous Estimation of Cefixime and Cloxacillin in Tablets - Khan, Suroor Ahmed; Lamba, H.S.; Rathour, Arvind; Budhwaar, Vikaas; Manjusha; Pawa, Rakesh; Sharma, Pankaj (Asian Journal of Chemistry, 2010)
A simple, fast precise and accurate, high performance liquid chromatographic method has been developed for the simultaneous determination of cefixime and cloxacilin in tablets. A kromasil C-18 RP (150 × 4.6 mm) X4μ column was used. The mobile phase used was mixture of buffer pH 6.5 and acetonitrile in 65:35 v/v. The flow rate was 1.2 mL/min and eluent was monitored at 225 nm. The retention times of cefixime and cloxacillin were 4.99 and 13.837, respectively. Recovery of cefixime and cloxacillin were 100.05 and 102%, respectively. The proposed method is precise, accurate selective, reproducible and rapid for the determination of cefixime and cloxacillin from marketed tablet formulation.